HUBUNGAN ANTARA GAYA KEPEMIMPINAN TRANSFORMASIONAL DENGAN ETOS KERJA PADA KARYAWAN NON MEDIS RS PKU MUHAMMADIYAH SURAKARTA - Putri, Daradinda Betayandiansari, Achmad Dwityanto, S.Psi, M.Si (2017)
Employee who has high work ethic can give positive influence for company because bring inovation while they work. Leader with transformational style be trusted to increase work ethic because motivate the employee's to make inovation. This study aims to determine the relationship between transformational leadership with work ethic in RS PKU Muhammadiyah Surakarta's non medic employees. The hypothesis of this study in there is a positive relationship between transformational leadership with work ethic in RS PKU Muhammadiyah Surakarta's non medic employees. The sampling technique of this study is proportional sampling. The population are all employees of RS PKU Muhammadiyah Surakarta amount to 299 peoples and sample in this research amount to 100 peoples. The data collection using transformasional leadership scale and work ethic scale. Data is analyzed by using product moment correlation on computer program named SPSS 22.00 version. The output of product moment analysis, resulted coefficient correlation = 0,616 with significance p=0,000; (p≤0,001). It's mean, there is a very significant posstive correlation between transformational leadership with work ethic. The contributions effective showed by value of (r2) = 0,37 that means the contribution effective transformational leadership to work ethic amount to 37 %. It is showed there is 63 % another variables that influence work ethic besides transformational leadership. The category of transformational leadership is belonging to high category with Empirical Average amount to 143, 37 and Hypotetic Average amount to 117,5. The category of work ethic is belonging to high category with Empirical Average amount to 79,17 and Hypotetic Average amount to 62,5. Keywords : transformational leadership, work ethic